Obtenção de carvão ativado a partir de lodo industrial para a remoção de contaminantes e recuperação de bioálcoois via adsorção - Streit, Angélica Fátima Mantelli (2021)
In this study, biological sludge, which is an abundant and problematic solid waste from the wastewater treatment plant (WTP) of a beverage industry, was used to prepare a high quality activated carbon (ACBS). This was investigated in the adsorption of contaminants (crystal violet, red 40, paracetamol, ibuprofen and ketoprofen) and in the recovery of bioalcohols (ethanol, propanol and butanol) in aqueous solutions. To obtain the adsorbent material, a synthesis route was adopted via pyrolysis and chemical activation (ZnCl2 and lime), where the pyrolyzed sludge (PS) originated. Subsequently, PS was subjected to a leaching with hydrochloric acid (HCl) and thus obtained the ACBS. These materials were characterized for their physicochemical properties and then applied to adsorption studies. The characterizations showed that ACBS is a mesoporous, semi-crystalline material that obtained the greatest surface area (631.8 m2 g - ¹), total pore volume (0.5098 cm3 g - ¹) and mean pore diameter (6.32 nm) when compared to PS. The SEM technique confirmed this increase in porosity, roughness and cavity formation in ACBS compared to PS. Through the Boehm Titration, a minimal amount of acid groups and no basic group was detected in ACBS, contrary to what was found in PS. The TG/DTG analyzes were consistent with the other characterization techniques, as a smaller residual mass was observed in ACBS (28%) than in PS (37%). Adsorption studies proved that ACBS is more suitable than PS for removing contaminants, as well as for recovering bioalcohols. In fact, ACBS has shown to have great potential in the removal and recovery of these chemical compounds in view of the high adsorption capacities detected for crystal violet (640.7 mg g − ¹), red 40 (287.1 mg g − ¹), acetaminophen (145.4 mg g − ¹), ibuprofen (105.9 mg g - ¹), ketoprofen (57.6 mg g - ¹), butanol (1801.70 mg g - ¹/ 24.64 mmol g - ¹), propanol (1107.63 mg g - ¹/ 19.31 mmol g - ¹) and ethanol (722.90 mg g - ¹/ 16.48 mmol g - ¹). In addition, adsorbent materials (PS and ACBS) from solid waste can be safely used for adsorption, as they did not show phytotoxic effects on Lactuca sativa. This effect also allowed us to verify that the toxicity of dyes can be significantly reduced using ACBS in the adsorption. In conclusion, the biological sludge used as a precursor material, as well as the synthesis method adopted, provided an adsorbent with excellent textural and chemical properties. Consequently, this ensured that ACBS can be used in different applications, such as in the case of contaminant removal and bioalcohol recovery via adsorption. Above all, the conversion of sludge to ACBS has multiple ecological prominence, as it contributes to solid waste management, removal of recalcitrant contaminants and lower energy consumption through the adsorption in the recovery of bioalcohols.